Socioeconomic disparities in multimorbidity of chronic diseases in the RaNCD cohort study - Roya Safari Faramani; Keyvan Samian; Farid Najafi; Yahya Salimi; Mitra Darbandi (Scientific Reports)
Abstract There is limited understanding of socioeconomic inequality in multimorbidity in Iran. This study aims to investigate socioeconomic inequality in multimorbidity among adults in western Iran. Data from the Ravansar Non-Communicable Disease (RaNCD) cohort study were used in this cross-sectional study. A sample of 10,047 adults aged 35–65 years was analyzed. Principal component analysis was utilized to determine socioeconomic status (SES). The normalized concentration index (NCI) was used to assess the extent of socioeconomic disparities in multimorbidity. Decomposition analysis was conducted to identify and calculate the factors contributing to multimorbidity inequality. In this study, the prevalence of having at least two NCDs was 9.07%, while the prevalence of having at least three NCDs was 2.87%, and four or more NCDs was 1.25%. The NCI for multimorbidity was -0.061 (P < 0.001), indicating a higher concentration of multimorbidity among individuals with low SES. Age (52.5%), body mass index (BMI) (29.4%), gender (27.5%), physical activity (25.1%), and SES (15%) were identified as significant factors contributing to the increased inequality in multimorbidity. The study findings identified age, gender, BMI, physical activity, and SES as key factors driving multimorbidity disparities. It is recommended that health policymakers prioritize health interventions aimed at reducing socioeconomic inequalities in multimorbidity, particularly for low-SES groups, women, obese individuals, and older adults.